2011
DOI: 10.1186/bcr2801
|View full text |Cite
|
Sign up to set email alerts
|

α-TEA cooperates with chemotherapeutic agents to induce apoptosis of p53 mutant, triple-negative human breast cancer cells via activating p73

Abstract: IntroductionSuccessful treatment of p53 mutant, triple-negative breast cancers (TNBC) remains a daunting challenge. Doxorubicin (DOXO) and cisplatin (CDDP) are standard-of-care treatments for TNBC, but eventually fail due to acquired drug resistance and toxicity. New treatments for overcoming drug resistance and toxicity in p53 mutant, TNBC are therefore badly needed. Unlike p53, p73 - a member of the p53 family - is usually not mutated in cancers and has been shown to regulate p53-mediated apoptotic signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…In contrast, the basal-like (e.g., MDA-MB-468 cells) and claudin-low subtypes (e.g., MDA-MB-231 cells) are less differentiated, difficult to treat with poor prognosis (Hastak et al, 2010; Holliday and Speirs, 2011). Often, basal-like and claudin-low tumors lack the estrogen (ER), progesterone (PR), and HER2 receptors, and are thus triple-negative (Hastak et al, 2010; Holliday and Speirs, 2011; Tiwary et al, 2011; Byrski et al, 2012). These tumors are fueled by BCSCs, are highly resistant to chemotherapy (Hastak et al, 2010; Tiwary et al, 2011), and are very proliferative with worst survival rates (Bosch et al, 2010; Hastak et al, 2010; Tiwary et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the basal-like (e.g., MDA-MB-468 cells) and claudin-low subtypes (e.g., MDA-MB-231 cells) are less differentiated, difficult to treat with poor prognosis (Hastak et al, 2010; Holliday and Speirs, 2011). Often, basal-like and claudin-low tumors lack the estrogen (ER), progesterone (PR), and HER2 receptors, and are thus triple-negative (Hastak et al, 2010; Holliday and Speirs, 2011; Tiwary et al, 2011; Byrski et al, 2012). These tumors are fueled by BCSCs, are highly resistant to chemotherapy (Hastak et al, 2010; Tiwary et al, 2011), and are very proliferative with worst survival rates (Bosch et al, 2010; Hastak et al, 2010; Tiwary et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Often, basal-like and claudin-low tumors lack the estrogen (ER), progesterone (PR), and HER2 receptors, and are thus triple-negative (Hastak et al, 2010; Holliday and Speirs, 2011; Tiwary et al, 2011; Byrski et al, 2012). These tumors are fueled by BCSCs, are highly resistant to chemotherapy (Hastak et al, 2010; Tiwary et al, 2011), and are very proliferative with worst survival rates (Bosch et al, 2010; Hastak et al, 2010; Tiwary et al, 2011). Thus, recent efforts have been focusing on treatments that may shift the less differentiated BCSCs toward a more differentiated phenotype, making them more susceptible to treatment options, and eliminating the chance for recurrence and/or metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published data have demonstrated that p73 may serve a critical role in the induction of cell death by apoptosis in various p53-deficient cancer cell lines, including TNBC 231 cells (7,(19)(20)(21). In order to understand the events involved in curcumol-mediated apoptosis of TNBC MDA-MB 231-cells, the present study investigated the expression patterns of p73 as well as of the p53-mediated pro-apoptotic mediators PUMA and Bcl-2 associated X protein (Bax) gene family, using immunoblotting.…”
Section: Curcumol Upregulates the Expression Of P73 Puma And Bakmentioning
confidence: 99%
“…p73 is a member of the p53 gene family. Under certain conditions, p73 is able to replace the p53 function in response to DNA damage, activate the transcription of p53-responsive genes and inhibit cell growth in a p53-like manner by inducing cell cycle arrest and apoptosis (6)(7)(8). Therefore, the identification of anticancer drugs able to activate p73 and target p53 downstream genes may provide a chemotherapeutic approach for the treatment of p53-deficient types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Rapamycin, in current use to inhibit this pathway in those tumors that show its activation, synergizes cisplatin sensitivity in basal‐like breast cancer cells through TP73 upregulation (Wong et al, ). Interestingly, natural compounds such as α‐TEA (Tiwary et al, ) and curcumin indirectly activate TAp73 transcription through the blockage of the mTOR pathway. Similarly, the green tea extract epigallocathechin‐3‐gallate (EGCG) and 1alpha,25‐dihydroxyvitamin D3 also activate TAp73 , inducing apoptosis and enhancing the effect of various chemotherapeutic drugs (Shammas et al, ; Ma et al, ; Onoda et al, ; Jørgensen et al, ; Achour et al, ).…”
Section: Introductionmentioning
confidence: 99%